Informativeness of ground penetrating radar method for investigations of the glaciers on Galindez, Winter and Skua Islands (the Argentine Islands, results for the period April to November 2017) - Chernov, A.P. (Український антарктичний журнал, 2017)
In this paper results of ground penetrating radar (GPR) surveying of island’s glaciers are shown. The main objectives were testing of VIY-3 300 GPR in weather conditions of Antarctica and check which information about glaciers can be obtained with this equipment. В роботі представлені результати георадарних досліджень острівних льодовиків. Мета досліджень: випробувати придатність георадара VIY-3 300 для роботи в умовах Антарктики та перевірити інформативність застосування даної апаратури для дослідження льодовиків. В данной работе представлены результаты георадарных исследований островных ледников. Цели работ. Тестирование георадара VIY-3 300 на работоспособность в условиях Антарктики, определение информативности оборудования для исследования ледников.